Re-reading of Kim Hwan-Tae’s Criticism in the 1930s: an Aestheticist’s ‘Disinterested’ Wait - Park, Hyunik (International Journal of Korean Humanities and Social Sciences, 2024)
This article examines the significance of Kim Hwan-tae’s literary criticism in the 1930s, focusing on the core principles of aestheticism and its connection to Park Yong-chul’s poetry. Kim Hwan-tae’s criticism of impressionism has been interpreted as an advocacy for the value of pure literature, serving as a counterpoint to the dogmatic criticism championed by KAPF in the 1920s. Discussions of his criticism have often focused on the influence of figures such as Matthew Arnold and Walter Pater. This study argues that Kim Hwan-tae’s promotion of impressionism or art supremacy constituted a strategic framework aimed at transforming the roles of both authors and critics, extending beyond mere opposition to the Korean Artists Proletariat Federation (KAPF) position. His emphasis on ‘humility (겸허/謙虛)’ and ‘discipline (수양/修養)’ as essential qualities for critics reflects his ideal of aestheticism. Moreover, the critic’s model he advocated, which prioritizes self-discipline and holistic cultivation of personality, draws on Romanticism’s ‘genius theory (천재론)’ and German cultural discourse (독일 교양론), making it a distinctive feature of Kim Hwan-tae’s criticism.